The impact of work commitment and motivation on the performance of nurses at Muyang Kute Hospital, Bener Meriah Regency - Jumiati, Jumiati; Hartono, Hartono; Ginting, Rapael; Wilvia, Wilvia; Setiawan, Linda Novelgia; Chiuman, Veranyca; Yuni, Yuni; Pratiwi, Tari Dwi (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
This study investigates the influence of work commitment and motivation on nurse performance at Muyang Kute Regional General Hospital, Bener Meriah Regency, Indonesia, using an analytical survey with a cross-sectional design. A total sampling of 49 nurses from inpatient wards participated in the study. Data were collected via questionnaires measuring work commitment (Guttman scale), work motivation (Guttman scale), and nurse performance (Likert scale). Bivariate analysis using Fisher’s Exact Test revealed a significant association between both work commitment and nurse performance (p = 0.000) and work motivation and nurse performance (p = 0.003). Nurses with high commitment demonstrated significantly higher performance, with 81.8% exhibiting high performance compared to 25.9% of nurses with low commitment. Similarly, nurses with high work motivation showed significantly higher performance, with 70.4% categorized as high performers compared to 27.3% of those with low motivation. These findings highlight the critical role of work commitment and motivation in enhancing nurse performance, suggesting that interventions aimed at improving these factors could lead to significant improvements in healthcare delivery at Muyang Kute Hospital. The study underscores the importance of addressing factors that influence nurse commitment and motivation to optimize patient outcomes and organizational success.